Using wavelets in applied electromagnetics : an algorithm for efficient pattern synthesis of linear aperture antennas - Cuiñas Gómez, Íñigo; Landesa, Luis; Rodríguez Pino, Marcos (Pontificia Universidad Católica del Perú, 1998)
Pattern synthesis of linear aperture antennas is a classical problem in Applied Electromagnetics with a great number of resolving methods. In this paper, a new algorithm that uses wavelets to compute the solution is presented. The new method reaches a good approximation of the aperture field from the antenna radiation pattern, using the Haar wavelet basis. Results prove the performance of the proposed method.
Keywords: Electromagnetismo; Radiación; Ondículas; Antenas; https://purl.org/pe-repo/ocde/ford#1.01.00